Mdma (3,4-Methylenedioxymethamphetamine) Analogues as Tools to Characterize Mdma-Like Effects: An Approach to Understand Entactogen Pharmacology - Hernandez-Kunstmann, A; Saez-Briones, P (2013)
Besides stimulants and hallucinogens, whose psychotropic effects are shared by many structurally related molecules exhibiting different efficacies and potencies in humans, the phenylisopropylamine MDMA (3,4-methylenedioxymethamphetamine, XTC, "Ecstasy") is the prototypical representative of a separate class of psychotropic substance, able to elicit the so-called entactogenic syndrome in healthy humans. This reversible altered state of consciousness, usually described as an "open mind state", may have relevant therapeutic applications, both in psychotherapy and as a pharmacological support in many neuropsychiatric disorders with a high rate of treatment failure. Nevertheless, a comprehensive and systematic exploration of the structure-activity relationships associated with entactogenic activity has remained incomplete and controversial, highlighting the possibility that MDMA might represent a pharmacological rarity in the field of psychotropics. As the latter is still an open question, the pharmacological characterization of MDMA analogues remains the logical strategy to attempt the elucidation of the structural requirements needed to elicit typical MDMA-like effects. Intriguingly, almost no experimental evidence supports the existence of actual MDMA analogues that truly resemble the whole pharmacological profile of MDMA, probably due to its complex (and partially not fully understood) mechanism of action that includes a disruption of monoaminergic neurotransmission. The present review presents a brief summary of the pharmacology of MDMA, followed by the evidence accumulated over the years regarding the characterization of classical structurally related MDMA analogues in different models and how this state of the art highlights the need to develop new and better MDMA analogues. © 2013 Bentham Science Publishers.